2014
DOI: 10.7848/ksgpc.2014.32.1.29
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Application of UAV for Korean Land Monitoring

Abstract: UAV(Unmanned Aerial vehicle) could be effectively applied in a field of land monitoring for analyzing disaster area and mapping, because it can quickly acquire image data at low costs. For this reason, we reviewed the legal system related to mapping, and proposed suggestions for improving in legal system, due to introducing the UAV to Korean land-monitoring through this paper. Also, we evaluated spatial and time accuracy of the digital map, which are generated from UAV images that were taken for occasional map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…They found that the average particle size on the beach was much larger than that of the sub-littoral zone. Kim and Song (2012) also obtained similar granulometric results using sand samples from several beaches of Gangwondo province, where the type locality of C.goseongensis sp. n. is located.…”
Section: Discussionsupporting
confidence: 61%
“…They found that the average particle size on the beach was much larger than that of the sub-littoral zone. Kim and Song (2012) also obtained similar granulometric results using sand samples from several beaches of Gangwondo province, where the type locality of C.goseongensis sp. n. is located.…”
Section: Discussionsupporting
confidence: 61%
“…Various studies have been conducted on using UAV images and photogrammetry for cadastral surveys (Kurczynski, 2016) over large areas and with a precision of 5-10 cm. Kim et al 2014 examined the effectively of UAV for land monitoring in order to analyze and detect disaster areas. They evaluated the accuracy of the digital maps generated from UAV images.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research, the advantages of UAV are as follows. First, unlike photos taken by manned aircrafts or satellites, UAV-based aerial photogrammetry accelerates data gathering and monitoring tasks (Unger, Reich, and Heipke 2014;Kim et al 2014;Kim, Yu, Park, and Ha 2008). Second, UAV-based aerial photogrammetry has advantages over manned aircrafts, artificial satellites, and 3D scanners in terms of convenience and costeffectiveness (Colomina et al 2008;Choi 2014a;Lee, Choi, and Joh 2015).…”
Section: Consideration For Automated Inspection For Occupancy Authorimentioning
confidence: 99%